Fostering global well-being: a new paradigm to revitalize agricultural and rural development - Bathrick, David D. (International Food Policy Research Institute, 1998)
In this paper, David Bathrick describes the almost revolutionary changes that have taken place in the economic arena in recent years. This is a story of paradigm shift, where government-led economic growth through the 1970s gave way to the increasingly market-led growth we see now. The emergence of the market in the context of globalization has meant the reduction of biases against agriculture; an emphasis on flexible responses in the production of goods and services; strengthened links between local, national, and international economies; greater integration of different sectors of the economy; and increased importance of the private sector. Bathrick argues that this demand- driven setting is forcing developing countries to assess their comparative advantages in the global marketplace and make fundamental strategic, institutional, and programmatic shifts. The resulting opportunities for growth are considerable, but so is the effort and financial support required to acquire the skills, experiences, and infrastructure necessary to adjust to the new realities. Knowledge of consumer needs, up-to-date market intelligence, and other informational and material resources that facilitate the market system need to be identified and put in place.